Measuring biomarkers in wastewater as a new source of epidemiological information: Current state and future perspectives. (February 2017) - Gracia-Lor, Emma; Castiglioni, Sara; Bade, Richard; Been, Frederic; Castrignanò, Erika; Covaci, Adrian; González-Mariño, Iria; Hapeshi, Evroula; Kasprzyk-Hordern, Barbara; Kinyua, Juliet; Lai, Foon Yin; Letzel, Thomas; et al.
Abstract: The information obtained from the chemical analysis of specific human excretion products (biomarkers) in urban wastewater can be used to estimate the exposure or consumption of the population under investigation to a defined substance. A proper biomarker can provide relevant information about lifestyle habits, health and wellbeing, but its selection is not an easy task as it should fulfil several specific requirements in order to be successfully employed. This paper aims to summarize the current knowledge related to the most relevant biomarkers used so far. In addition, some potential wastewater biomarkers that could be used for future applications were evaluated. For this purpose, representative chemical classes have been chosen and grouped in four main categories: (i) those that provide estimates of lifestyle factors and substance use, (ii) those used to estimate the exposure to toxicants present in the environment and food, (iii) those that have the potential to provide information about public health and illness and (iv) those used to estimate the population size. To facilitate the evaluation of the eligibility of a compound as a biomarker, information, when available, on stability in urine and wastewater and pharmacokinetic data (i.e. metabolism and urinary excretion profile) has been reviewed. Finally, several needs and recommendations for future research are proposed. Highlights: Wastewater biomarkers provide information on lifestyle habits, health and wellbeing. Specific criteria should be followed to select a suitable biomarker. Report of the current knowledge of the most relevant biomarkers used so far Proposal of potential wastewater biomarkers for future applications Review of pharmacokinetic data and stability in urine and wastewater for each biomarker